1987
DOI: 10.1086/209082
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Imagery in Information Processing: Review and Extensions

Abstract: Mental imagery is receiving increased attention in consumer behavior theory and research. This article describes imagery, characterizing it as a processing mode in which multisensory information is represented in a gestalt form in working memory and discusses research on the unique effects of imagery at low levels of cognitive elaboration. It specifies researchable propositions for the relationship between high elaboration imagery processing and consumer choice and consumption behaviors Finally, it reviews spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
689
5
55

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 970 publications
(770 citation statements)
references
References 114 publications
21
689
5
55
Order By: Relevance
“…Bloch and Richins (1983) postulate that hedonic values are characterized by heightened arousal, excitement, adventure and entertainment. Shopping behaviour provides excitement whereas the consumer interacts with the store environment and gives cues while they examine products ( Maclnnis and Price, 1987 ) that may be perceived as enjoyment.…”
Section: Literature Review Hedonic and Utilitarian Shopping Valuesmentioning
confidence: 99%
“…Bloch and Richins (1983) postulate that hedonic values are characterized by heightened arousal, excitement, adventure and entertainment. Shopping behaviour provides excitement whereas the consumer interacts with the store environment and gives cues while they examine products ( Maclnnis and Price, 1987 ) that may be perceived as enjoyment.…”
Section: Literature Review Hedonic and Utilitarian Shopping Valuesmentioning
confidence: 99%
“…Alesandrini (1983) argued that pictures not only highlight the message topic and its key points to the readers, but also conduce to catch the readers' attention [24]. Empirical studies have indicated pictures' superiority in memorability compared with words [25], [26]. Therefor, illustration is a critical complement to the headline and body copy of an advertisement, and assists the consumers' information processing and decision making [15].…”
Section: Illustrations Of Advertisementsmentioning
confidence: 99%
“…Abstract representation is somewhat alien for East Asians; they will therefore embody abstract cues with specific contexts (Cousins, 1989). For East Asians, imagery generation involves retrieval of past experience (Yuille and Catchpole, 1977); scenes of specific daily contexts retrieved from memory will create concrete imagery even in face of abstract cues (MacInnis and Price, 1987). Westerners are likely to generate more imagery when processing concrete ads than abstract ads, which is unlikely to happen in the case of East Asians.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The nature and amount of imagery generation can be altered by "priming" subjects or by providing them with specific "instructions to imagine" (MacInnis and Price, 1987). Just because Westerners are conditioned to think in abstract terms does not mean that only abstract information is stored in their memory.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation